Integrated Artificial Intelligence Mentoring to Enhance Teacher Competence at SMP Negeri 12 Banjarbaru - Lissa, Hermei; Hijriati, Na'imah; Abdurrahman, Saman; Idris, Moch; Lestia, Aprida Siska; Shiddiq, Muhammad Mahfuzh; Sa’adh, Yalela; Oktaviani, Yeni Rahma (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
The integration of Artificial Intelligence (AI) in school learning can enhance instructional quality and efficiency; however, its use by teachers remains fragmented. This community development activity, conducted by the Department of Mathematics at Universitas Lambung Mangkurat, aimed to improve teachers’ knowledge and skills through training and mentoring that emphasized the integrated use of ChatGPT, Gamma AI, and Presentations.AI. The program was implemented at SMP Negeri 12 Banjarbaru, Indonesia, involving teachers from various subject areas. Activities included AI-based training, hands-on mentoring, and pre- and post-activity evaluation. Data were analyzed using the Wilcoxon Signed-Rank Test. Results showed that improvements related to ChatGPT were not statistically significant (p > 0.05), whereas improvements with Gamma AI were statistically significant (p < 0.05). Improvements in Presentations.AI usage and integrated AI application skills were highly significant (p < 0.01). These findings indicate that integrated AI-based mentoring effectively enhances teacher competence at the junior high school level.